The Legal Status of Traditional Law in the Mongolian Legal System - Kuukhlee, Odontuya (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
This article explores the position of traditional law within Mongolia’s current legal system by comparing it with the roles traditional legal systems play in other legal families around the world. It highlights how the influence and function of traditional law vary across countries based on their unique historical, cultural, and legal developments. The study notes that while traditional law served an essential regulatory function in Mongolia’s past, today it is preserved mainly in symbolic and cultural forms within the Constitution and other legal documents, without holding binding legal authority. Furthermore, it discusses the challenges of translating legal terminology into English, which often leads to ambiguity among scholars. The findings suggest that traditional law, though no longer a normative source of regulation, continues to reflect Mongolia’s national identity and historical continuity within the legal framework. Although the terms ‘legal tradition’ and ‘traditional law’ are often translated into Mongolian using the same or similar words – thereby creating ambiguity – the two concepts are clearly distinguishable in terms of their scope and meaning. In Mongolia’s legal sources, there is no official legal terminology equivalent to ‘indigenous law’ or ‘local law,’ and customary law is not formally applied at the legal or regulatory level. Within the field of legal studies, customary norms are generally regarded as informal or non-codified sources of regulation.